(untitled) (Research, Society and Development, 2023)
Eating disorders are characterized by disturbances in eating behavior, which mainly affect adolescents and young women. They are multifactorial psychiatric diseases causing clinical, emotional and social damage, which leads to extreme weight loss, obesity in addition to increased morbidity and mortality. The objective of this research was to identify the social, psychological and family factors that may contribute to BAD - Disorder of Binge Eating in adolescents. This study is a literature review research. A bibliographical study was intended to be carried out. From the theoretical foundation, the application of knowledge into information about eating disorders began. And finally, through the results obtained, it was possible to identify factors that affect adolescents in binge eating. From the results, it was possible to identify that eating disorders in female adolescents have social, psychological and family risk factors, which highlights the complexity of the disorders and how they can be influenced by multiple aspects of the adolescents’ lives. In short, this study highlights the complexity of the disorders and their significant impact on physical and mental health. Multidisciplinary and preventative approaches are needed to effectively address these issues and promote the well-being of affected individuals. It has contributed to our understanding of disorders and their impacts on adolescent girls. It is essential that we are aware of these findings to provide effective and holistic care for people affected by eating disorders.